2019
DOI: 10.1177/0145482x19865382
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Orientation and Mobility Specialist Students Who are Blind and Have Low Vision: Survey of Faculty Who Teach Blindfold and Simulation Cane Courses

Abstract: Introduction: The purpose of this study was to survey the faculty of personnel preparation programs that train orientation and mobility (O&M) specialists in the identification of accommodations, teaching techniques, and resources needed to teach students who are visually impaired (i.e., those who are blind or have low vision) and who are enrolled in blindfold and simulation cane courses (hereafter, cane courses). Cane courses are used to teach the techniques of independent cane travel, and they require tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Aspects of this study were similar to aspects of the initial study by Griffin-Shirley et al (2019), including smaller faculty-to-student ratios for blindfold simulation cane courses, the accommodations used by the participants when they were students (e.g., readers, materials provided in braille, and computers for assignments), and tips for monitoring students' safety (see Table 5 for a list of the teaching strategies). The participants reported faculty-to-student ratios for their blindfold simulation cane courses of 1:2 and 1:4, while Griffin-Shirley et al (2019) reported instructor-tostudent ratios of 1:4 and 1:6.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Aspects of this study were similar to aspects of the initial study by Griffin-Shirley et al (2019), including smaller faculty-to-student ratios for blindfold simulation cane courses, the accommodations used by the participants when they were students (e.g., readers, materials provided in braille, and computers for assignments), and tips for monitoring students' safety (see Table 5 for a list of the teaching strategies). The participants reported faculty-to-student ratios for their blindfold simulation cane courses of 1:2 and 1:4, while Griffin-Shirley et al (2019) reported instructor-tostudent ratios of 1:4 and 1:6.…”
Section: Discussionmentioning
confidence: 99%
“…Aspects of this study were similar to aspects of the initial study by Griffin-Shirley et al (2019), including smaller faculty-to-student ratios for blindfold simulation cane courses, the accommodations used by the participants when they were students (e.g., readers, materials provided in braille, and computers for assignments), and tips for monitoring students' safety (see Table 5 for a list of the teaching strategies). The participants reported faculty-to-student ratios for their blindfold simulation cane courses of 1:2 and 1:4, while Griffin-Shirley et al (2019) reported instructor-tostudent ratios of 1:4 and 1:6. Participants reported engaging in between 400 and 1,300 hours of blindfold immersion training in their university programs, far more hours than did the participants of Griffin-Shirley et al (2019) research (they reported meeting between 1 and 14 hours per week over the course of one or two semesters).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations